Culturomics- and metagenomics-based insights into the microbial community and function of rhizosphere soils in Sinai desert farming systems - Wen-Hui Lian; Osama Abdalla Abdelshafy Mohamad; Lei Dong; Ling-Yu Zhang; Dong Wang; Lan Liu; Ming-Xian Han; Shuai Li; Shuang Wang; André Antunes; Bao-Zhu Fang; Jian-Yu Jiao; et al. (Environmental Microbiome, 2023)
Abstract Background The microbiome of the Sinai Desert farming system plays an important role in the adaptive strategy of growing crops in a harsh, poly-extreme, desert environment. However, the diversity and function of microbial communities under this unfavorable moisture and nutritional conditions have not yet been investigated. Based on culturomic and metagenomic methods, we analyzed the microbial diversity and function of a total of fourteen rhizosphere soil samples (collected from twelve plants in four farms of the Sinai desert), which may provide a valuable and meaningful guidance for the design of microbial inoculants. Results The results revealed a wide range of microbial taxa, including a high proportion of novel undescribed lineages. The composition of the rhizosphere microbial communities differed according to the sampling sites, despite similarities or differences in floristics. Whereas, the functional features of rhizosphere microbiomes were significantly similar in different sampling sites, although the microbial communities and the plant hosts themselves were different. Importantly, microorganisms involved in ecosystem functions are different between the sampling sites, for example nitrogen fixation was prevalent in all sample sites while microorganisms responsible for this process were different. Conclusion Here, we provide the first characterization of microbial communities and functions of rhizosphere soil from the Sinai desert farming systems and highlight its unexpectedly high diversity. This study provides evidence that the key microorganisms involved in ecosystem functions are different between sampling sites with different environment conditions, emphasizing the importance of the functional microbiomes of rhizosphere microbial communities. Furthermore, we suggest that microbial inoculants to be used in future agricultural production should select microorganisms that can be involved in plant-microorganism interactions and are already adapted to a similar environmental setting.